2021
DOI: 10.29333/iji.2021.1425a
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Aggression between Intentions and Cyber Wellness of Students: An application of TPB Models

Abstract: This exploratory study aims to broaden students' models of cyber-aggression behavior, with the Theory of Planned Behavior (TPB) by including additional constructs, namely cyber health, to predict youth cyber-aggression actions. The self-administered questionnaire was used to collect data from 291 students intentionally, aged 15 to 21 at secondary schools in the city of Padang in Indonesia, and then analyzed using covariance-based structural equation modeling (SEM). Data analysis was performed using WarpPLS sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…Despite the fact that bullying is not perceived as something that consistently affects academic performance, there is another type of violence that does manifest itself as an obstacle to educational achievement: structural violence translated into poverty, which had already been found in the studies by McKensie (2019), Burdick-Will (2018), Rutkowski et al (2018) and Croizet et al (2017). Even though bullying is not perceived by educational actors themselves as a significant cause of low educational achievement, it is observed that this has a negative impact on the emotional health of students and teachers, as pointed out by authors such as Rutkowski et al (2013), Mardianto et al (2021) and Frugård Strøm (2014, as well as affects the dislike for school and that may have even greater implications for permanence in future educational levels.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Despite the fact that bullying is not perceived as something that consistently affects academic performance, there is another type of violence that does manifest itself as an obstacle to educational achievement: structural violence translated into poverty, which had already been found in the studies by McKensie (2019), Burdick-Will (2018), Rutkowski et al (2018) and Croizet et al (2017). Even though bullying is not perceived by educational actors themselves as a significant cause of low educational achievement, it is observed that this has a negative impact on the emotional health of students and teachers, as pointed out by authors such as Rutkowski et al (2013), Mardianto et al (2021) and Frugård Strøm (2014, as well as affects the dislike for school and that may have even greater implications for permanence in future educational levels.…”
Section: Discussionmentioning
confidence: 88%
“…As previously noted, some research has pointed to an explanatory chain of the negative effect of bullying on academic achievement, with the emotional effects being the bridge that unites these two elements. Mardianto et al (2021) founded a strong positive relationship between adolescent attitudes towards cyber aggression and their behavioral intentions to do so, therefore, the subjective interpretation of the aggression determine the emotional response, following from this, Frugård Strøm (2014) states that bullying causes low self-esteem, low self-efficacy, depression, anxiety and suicidal ideas, as well as poor academic performance. Bullied children and adolescents are more likely to perform worse in school compared to students who are not bullied and, in the long term, this has an impact on future school options, such as college completion.…”
Section: Introductionmentioning
confidence: 99%
“…Lebih lanjut Cyber wellness dapat diartikan sebagai kesejahteraan positif pengguna Internet dan budaya dunia maya yang sehat untuk komunitas Internet (Putnam & Pulcher, 2007). Sementara itu Menurut Mardianto (2019), konsep cyber wellness melibatkan pemahaman individu terhadap perilaku online dan kesadaran akan cara melindungi diri di lingkungan digital. Fokus utamanya adalah mengarahkan individu untuk bertanggung jawab atas tindakan mereka saat berada di dunia maya dan menjadi pembelajar digital yang baik.…”
Section: Pendahuluanunclassified
“…Although both men and women are impacted by technology-facilitated GBV, women and girls in Asia face online gender-based and sexual harassment at disproportionately higher rates compared to their male peers (Cai et al, 2021; Gurumurthy, Vasudevan, Chami & Mahesh, 2019; Koirala, 2020; Kovacs et al, 2013; Plan International and Save the Children, 2020; UN Women, 2020; Xu, 2010). Online acts of violent behaviors are most often conducted by men (Devika et al, 2019; Mardianto et al, 2019; Marret & Choo, 2017), although this trend varies depending on the form of technology-facilitated violence.…”
Section: Key Findingsmentioning
confidence: 99%